Prediksi Erosi Tanah Dengan Menggunakan Metode Universal Soil Loss Equation Di Bagian Tengah-Hilir Das Oba - Irawati Karim; Adnan Sofyan; Lily Ishak (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2022)
The Oba watershed is one of the watershed located in the City of Tidore Islands where in the middle-downstream it has a shallow river so that when it rains continuously with high intensity it will cause flooding. In addition, it has a complex topography from flat to hilly where most of the area has steep slopes (25-45%) so the potential for erosion is very large. The aims of the research are: 1) to analyze the amount of erosion in the middle-downstream part of the Oba watershed; and 2) identify soil conservation management efforts in the mid-downstream part of the Oba watershed. Prediction of soil erosion using the Universal Soil Loss Equation (USLE) method. The results showed that: 1) the level of danger of soil erosion that occurred included: a) very light erosion (12.45 tons/ha/year) occurring on a slope of 8-15% covering an area of ​​562.1 ha (2.1%); b) mild erosion (0.40–27.43 tons/ha/year) occurring on slopes of 0-8% and slopes >45% covering an area of ​​1.575 (37.9%); c) Moderate erosion (149.93 – 153.32 tons/ha/year) occurs on slopes of 8-15% and slopes of 15-25% covering an area of ​​2,489.8 (60%) of the total area of ​​the middle-downstream part of the Oba watershed; and 2) soil conservation management efforts include alternating corn + cassava and peanuts at SPL-18 with a slope of 15-25% and at SPL-25 with a slope of 25-45%, then without alternatives on a slope of 0-8%. , 8-15% and >45%.